Integrative Leadership in a Bachelor of Science in Nursing–Integrative Health Program. - Baumhover, Nancy (Nurse Leader, 2020)
Integrative nursing leadership blends appreciative, relational, authentic, mindful, transformational, and compassionate leadership styles. Integrative nursing leadership comprises the following 7 tenets: beginner's mind, meaningful relationships, authenticity, role modeling, gratitude, whole-person and whole-team care, and the use of team integrative modalities. Clinical nurse leaders may want to consider adopting integrative nursing leadership to adequately lead a nursing workforce interested in transforming health care into a more holistic (bodymindspirit) interprofessional care model.